Sustainable Plant-Based Fibres and Nonwoven Systems: Mechanical, Processing, and Environmental Perspectives for Textile and Technical Applications - Dr. Marie Thompson (The American Journal of Engineering and Technology, 2025)
Background: The growing demand for sustainable and environmentally friendly materials has intensified interest in plant-based fibres and their integration into nonwoven systems for textile and technical applications (Ali & Sarw, 2010). Plant fibres such as flax, hemp, alfa, and bamboo present favorable mechanical and environmental attributes, yet their variability, processing challenges, and performance in nonwoven structures demand rigorous multidisciplinary investigation (Hearle & Morton, 2008; Smole et al., 2013). This research synthesizes theoretical foundations, testing standards, material selection frameworks, and processing considerations to produce an integrated understanding of plant-fibre-based nonwovens and their application potential (Kalebek & Babaarslan, 2016; Turbak, 1993). Methods: The study adopts a comprehensive, literature-grounded methodological synthesis: critical appraisal of standardized testing protocols for fibres (ASTM, 1962–1964; BIS, 1971), mechanistic interpretation of fibre structure–property relations (Bledzki et al., 2006; Hearle & Morton, 2008), and comparative analysis of nonwoven formation technologies and blend strategies (Turbak, 1993; Russell, 2006). Emphasis is placed on mapping fibre selection criteria to nonwoven process windows, elucidating the influence of fibre geometry, surface chemistry, and treatment on mechanical and functional performance (Ghali et al., 2014; Albrecht et al., 2006). Results: Synthesis indicates that controlled fibre morphology (length, fineness, lumen structure) and pre-processing (retting, mechanical extraction, refining) are decisive for nonwoven web cohesion and performance (Bledzki et al., 2006; Hearle & Morton, 2008). Blending plant fibres with thermoplastic or natural binders improves web integrity but requires optimization of fibre–binder interactions to preserve biodegradability and desired mechanical properties (Ghali et al., 2014; Kalebek & Babaarslan, 2016). Standardized test metrics (breaking load, elongation, conditioning) provide reproducible comparators, yet must be contextualized for anisotropic, heterogeneous plant-fibre assemblies (ASTM, 1962–1964; BIS, 1971; Booth, 1968). Conclusion: Plant-fibre nonwovens are viable alternatives for a broad set of textile and technical applications when design is informed by fibre-selection frameworks, rigorous conditioning and testing, process–material coupling, and explicit environmental assessments (Smole et al., 2013; Russell, 2006). Future research must prioritize scalable pre-processing routes that reduce variability, binder chemistries that balance performance and sustainability, and standardization of testing regimes tailored to plant-based nonwovens. This integrative perspective advances the technical readiness of sustainable nonwoven systems and delineates key research pathways for industrial adoption.